2012
DOI: 10.1042/cs20110668
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of diabetes and ACE2 in the pathogenesis of cardiovascular disease in experimental diabetes

Abstract: Local and systemic AngII (angiotensin II) levels are regulated by ACE2 (angiotensin-converting enzyme 2), which is reduced in diabetic tissues. In the present study, we examine the effect of ACE2 deficiency on the early cardiac and vascular changes associated with experimental diabetes. Streptozotocin diabetes was induced in male C57BL6 mice and Ace2-KO (knockout) mice, and markers of RAS (renin-angiotensin system) activity, cardiac function and injury were assessed after 10 weeks. In a second protocol, diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
4
33
0
1
Order By: Relevance
“…135 Further studies have validated our findings for this essential role of ACE2 in diabetic cardiomyopathy. 136, 138140, 144 We also identified beneficial effects of Ang 1–7 in type 2 diabetic cardiomyopathy. By reducing cardiac hypertrophy, lipotoxicity, and adipose inflammation, in combination with increased adipose triglyceride lipase, Ang 1–7 completely rescued diastolic dysfunction in the db/db type 2 diabetic murine model.…”
Section: Role Of Ace2/ang 1–7 In Hfmentioning
confidence: 73%
“…135 Further studies have validated our findings for this essential role of ACE2 in diabetic cardiomyopathy. 136, 138140, 144 We also identified beneficial effects of Ang 1–7 in type 2 diabetic cardiomyopathy. By reducing cardiac hypertrophy, lipotoxicity, and adipose inflammation, in combination with increased adipose triglyceride lipase, Ang 1–7 completely rescued diastolic dysfunction in the db/db type 2 diabetic murine model.…”
Section: Role Of Ace2/ang 1–7 In Hfmentioning
confidence: 73%
“…There is controversy about the development of hypertension in db/db mice as some studies reported an increase [30], [31], while others reported no change in blood pressure [19], [32]. The hypertension observed by some investigators has been attributed to increased plasma AngII levels secondary to changes in angiotensin converting enzyme [31] and angiotensin converting enzyme-2 [33] activity in diabetic animals. In the present study blood pressure was not elevated in awake 14–18 wks old diabetic db/db mice as compared to age-matched non-diabetic db/+ controls.…”
Section: Discussionmentioning
confidence: 99%
“…They found that treatment of STZ-induced Type 1 diabetic rats with XNT, an ACE2 activator, resulted in increased ACE2/ACE mRNA and protein as well activity levels, along with decreased AT 1 R expression, which was associated with inhibition of ERK1/2 (extracellular-signal-regulated kinases 1/2), AMPKα (AMP-activated protein kinase α) and AMPKβ expression. Tikellis et al [91] found decreased myocardial ACE2 expression and Ang-(1-7) levels with increased circulating AngII levels in STZ-treated Type 1 diabetic mice, resulting in thinning of the LV wall and mild ventricular dilation associated with increased apoptosis and myocyte hypertrophy. Interestingly, DX-600 as well as A779 treatment in STZ-treated rats augmented the Type-1-diabetes-induced NADPH oxidase activation in cardiac tissue, resulting in ROS-production-induced cardiac dysfunction, where these effects were reversed by pretreatment with captopril or losartan [88].…”
Section: Heart Diseasementioning
confidence: 99%
“…XNT also inhibited STZ-induced hyperglycaemia [86] and improved autonomic function [87], resulting in improved cardiac function, decreased blood pressure and cardiac fibrosis. In contrast, at the same time the major phenotypic differences between ACE2KO and WT (wild-type) mice with respect to blood pressure and cardiac hypertrophy were eliminated following the induction of diabetes [91]. Tikellis et al [91] found decreased myocardial ACE2 expression and Ang-(1-7) levels with increased circulating AngII levels in STZ-treated Type 1 diabetic mice, resulting in thinning of the LV wall and mild ventricular dilation associated with increased apoptosis and myocyte hypertrophy.…”
Section: Heart Diseasementioning
confidence: 99%